Financial stability in the system management of business structures - O. B. Repkina (Путеводитель предпринимателя, 2020)
The article deals with the problem of assessing the financial soundness of the enterprises taking into account peculiarities of business structures; value and estimates of financial stability in crisis management; main approaches to identify the factors crisis state companies; Factors crisis state the nature and significance of crisis management for the sustainable development of enterprise structures.